REVITALISASI WADUK CIPTA KARYA KECAMATAN TAMPAN DALAM MENJAGA FUNGSI DAN PELESTARIAN LINGKUNGAN - Wulan Sri Rahayu; Zulkarnaini Zulkarnaini; Ferry Fatnanta (Program Pascasarjana Universitas Riau, 2015)
ABSTRACTThe purpose of this study was to determine the capacity of the Waduk Cipta Karya as much garbage and sediment into the reservoir, the problems that occur in the Waduk Cipta Karya and revitalizing Waduk Cipta Karya. This study was conducted in approximately Waduk Cipta Karya because although this reservoir has been constructed for the reduction of the flooding that occurred in District Tampan, but floods still occur when it rains.The results showed that the capacity of the Waduk Cipta Karya has declined This is because the waste and sedimentation in reservoirs. problems that occur in the Waduk Cipta Karya is the number of bins that are in dams and reservoirs supporting facilities are poorly maintained, and the revitalization efforts that can be done by the government and the public about the form of the arrangement of drainage and improvement of waterways, sediment control, provision of counseling and guidance to the community around reservoirs and land use regulation. Factors that cause inundation and flooding in District Tampan is the absence of water infiltration due to changes in land use and habits of the people who throw garbage into the waterways.